Sociological paths: from progress to interdisciplinarity - Jesús Alberto Valero Matas; Juan Romay Coca; Francesca Randazzo (FahrenHouse, 2017)
This work is a desk study on the beginnings of sociology as a science and the initial theoretical nature. We depart from the Enlightenment and its modern influence. However, we suggest that one of the greatest engines of epistemic transformation of sociology has been the notion of progress, overshadowed by other concepts today. Later we take a disciplinary path within the social sciences, raising mutual influences and considerations with Political Theory, Economics and Epistemology. The attempt to explain human thought and behavior from other social and disciplinary contexts seems to dethrone Sociology's own autonomous work of thought. However, sociology, as well as other human sciences, is a multidimensional discipline.